A novel risk calculator predicting surgical site infection after spinal surgery in patients with cerebral palsy. (28th February 2022) - Matsumoto, Hiroko; Franzone, Jeanne M.; Sinha, Rishi; Roye, Benjamin D.; Glotzbeker, Michael P.; Skaggs, David L.; Flynn, John M.; Lenke, Lawrence G.; Sponseller, Paul D.; Vitale, Michael G.
Abstract: Aim: To develop and validate a risk calculator based on preoperative factors to predict the probability of surgical site infection (SSI) in patients with cerebral palsy (CP) undergoing spinal surgery. Method: This was a multicenter retrospective cohort study of pediatric patients with CP who underwent spinal fusion. In the development stage, preoperative known factors were collected, and a risk calculator was developed by comparing multiple models and choosing the model with the highest discrimination and calibration abilities. This model was then tested with a separate population in the validation stage. Results: Among the 255 patients in the development stage, risk of SSI was 11%. A final prediction model included non‐ambulatory status (odds ratio [OR] 4.0), diaper dependence (OR 2.5), age younger than 12 years (OR 2.5), major coronal curve magnitude greater than 90° (OR 1.3), behavioral disorder/delay (OR 1.3), and revision surgery (OR 1.3) as risk factors. This model had a predictive ability of 73.4% for SSI, along with excellent calibration ability ( p = 0.878). Among the 390 patients in the validation stage, risk of SSI was 8.2%. The discrimination of the model in the validation phase was 0.743 and calibration was p = 0.435, indicating 74.3% predictive ability and no difference between predicted and observed values. Interpretation: This study provides a risk calculator to identify the risk of SSI after spine surgery for patients with CP. This will allow us to enhance decision‐making and patient care while providing valid hospital comparisons, public reporting mechanisms, and reimbursement determinations.